Association between Meniere’s disease and air pollution in South Korea - Lee, Dong-Han; Han, Jiyeon; Jang, Myoung-jin; Suh, Myung-Whan; Lee, Jun Ho; Oh, Seung Ha; Park, Moo Kyun (Scientific reports, 2021)
Meniere’s disease is thought to be a disorder of the inner ear function, affected by genetic and environmental factors. Several recent studies have shown that air pollution could affect middle and inner ear diseases. The purpose of this study was to investigate the relationship between the Meniere’s disease occurrence and air pollution status in Korea. This study used a time-stratified case-crossover design. Hospital visit data by Meniere’s disease were collected from the Korea National Health Insurance Service-National Sample Cohort (NHIS-NSC) database. Daily air pollution data for sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), carbon monoxide (CO), ozone (O 3 ), and particulate matter (PM 10 : ≤ 10 μm in diameter, and PM 2.5 : ≤ 2.5 μm in diameter) were collected from the National Ambient air quality Monitoring Information System (NAMIS) database. We used two-stage analysis to assess the association between degree of air pollution and the occurrence of Meniere’s disease. In the first stage, region-specific analysis was conducted to estimate the odds ratios (ORs) of Meniere’s disease risk associated with each air pollutant exposure by using conditional logistic regression for matched case–control sets in 16 regions. In the second stage, region-specific ORs from the first stage were combined and the pooled effect estimates were derived through fixed and random effect meta-analysis. Subgroup analysis was conducted for age, sex, seasonality, and urbanization of residence. In total, 29,646 (32.1% males and 67.9% females) Meniere’s disease cases were identified from Korea NHIS-NSC database between 2008 and 2015. Overall, SO 2 , NO 2 , CO, and PM 10 showed significant correlation with Meniere’s disease risk at immediate lags, and weaker correlation at delayed lags, whereas O 3 showed slightly negative correlation at the immediate lag (lag0) and PM 2.5 did not show strong correlation (SO 2 : 1.04 [95% confidence interval: 1.01, 1.06]; NO 2 : 1.08 [1.06, 1.11]; CO: 1.04 [1.02, 1.06]; O 3 : 0.96 [0.93, 0.99]: statistically significant ORs at lag0 are listed). These positive and negative associations between Meniere’s disease and each air pollutant were generally stronger in the age of 40–64, female, summer (June–August) season, and urban subgroups. Our results showed that hospital visits for Meniere’s disease were associated with the measured concentrations of ambient air pollutants SO 2 , NO 2 , CO, and PM 10 . Further studies are required to confirm these associations and find their mechanisms.